Priorities Setting with Foresight in South Africa - Anastassios Pouris; Portia Raphasha (Foresight and STI Governance)
South Africa has only irregularly undertaken exercises to identify priority technology areas, despite government recognition of their importance. Moreover this activity has no institutional frameworks. This article reviews past efforts in this field in South Africa. In the end of 1990s, the Department of Arts Culture, Science and Technology announced the results of the National Research and Technology Foresight. One of the key implications of these results was that, in contrast to the rest of the world, South African stakeholders fail to recognize the importance of emerging technologies such as nanotechnology, micro-production as well as simulation technologies as cost-effective components of new product and process development. These results appear to have permeated through the STI policy and as a result, the country appears to be lagging in terms of research in emerging technologies. The main focus of the authors is on the findings of the most recent effort supported by the Department of Trade and Industry to identify changes in industrialists’ opinions related to technology priorities. The recent results indicate that the country is integrating into the global economy, as national priorities are converging with priorities elsewhere.